Achievement of Vancomycin Therapeutic Goals in Critically Ill Patients: Early Individualization May Be Beneficial - Bita Shahrami; Farhad Najmeddin; Sarah Mousavi; Arezoo Ahmadi; Mohammad Reza Rouini; Kourosh Sadeghi; Mojtaba Mojtahedzadeh (Critical Care Research and Practice)
Objective. The aim of our study was to assess and validate the effectiveness of early dose adjustment of vancomycin based on first dose monitoring in achieving target recommended goal in critically ill patients. Methods. Twenty critically ill patients with sepsis received loading dose of 25 mg/kg of vancomycin and then were randomly assigned to 2 groups. Group 1 received maximum empirical doses of vancomycin of 15 mg/kg every 8 hrs. In group 2, the doses were individualized based on serum concentrations of vancomycin. First dose nonsteady state sampling was used to calculate pharmacokinetic parameters of the patients within 24 hours. Results. Steady state trough serum concentrations were significantly higher in group 2 in comparison with group 1 (19.4 ± 4.4 mg/L versus 14.4 ± 4.3 mg/L) (P=0.03). Steady state AUCs were significantly higher in group 2 compared with group 1 (665.9 ± 136.5 mg·hr/L versus 490.7 ± 101.1 mg·hr/L) (P=0.008). Conclusions. With early individualized dosing regimen, significantly more patients achieved peak and trough steady state concentrations. In the context of pharmacokinetic/pharmacodynamic goal of area under the time concentration curve to minimum inhibitory concentration (AUC/MIC) ≥400 and also to obtain trough serum concentration of vancomycin of ≥15 mg/L, it is necessary to individualize doses of vancomycin in critically ill patients.